Breast hamartoma: An underrecognized entity - Deshmukh, Satish; Fulare, Sushrut; Nagre, Akshay; Chowksey, Sanjeev (Indian Journal of Case Reports, 2018)
Hamartoma is a rare benign tumor of the breast. Pathologically, hamartomas are also labeled as lipofibroadenoma, fibroadenolipoma, or adenolipoma. This is due to a benign proliferation of the fibrous, glandular, and fatty component of the breast tissue surrounded by connective tissue capsule. Here, we report the case of a 60-year-old female patient who presented with a lump in the left breast for 4 months. Fine-needle aspiration cytology suggested the entity to be a benign cystic lesion. Lumpectomy was done and the cut surface showed cystic and solid areas. Histopathological examination revealed several irregular tissue fragments showing mammary glandular tissue with a prominent lobular arrangement, fibrous stroma, and fibroadipose tissue with the presence of papillary metaplasia at few places and confirmed it to be the hamartoma of the left breast.